OPTIMALISASI DIKMAS LANTAS SATUAN LALU LINTAS POLRES CIANJUR OLEH UNIT DIKYASA UNTUK MENGURANGI ANGKA PELANGGARAN LALU LINTAS OLEH KARYAWAN SWASTA DI WILAYAH KABUPATEN CIANJUR - Tantowi, Aditama (Advances in Police Science Research Journal, 2020)
One of the problems faced in a densely populated city is heavy traffic, which will lead to traffic violations. Traffic violations can be done by various groups, such as private employees. The legal area of the Cianjur Regional Police increases each year the number of motor vehicle violations is increasing, based on data from the Cops of the Traffic Unit of the Cianjur Regional Police in 2015 to 2019 the number of violations to private employees is increasing and does not show a decrease. So that preventive efforts must be carried out by the Cianjur Regional Police Unit Dikyasa in the implementation of the Dikmas Lantas to private employees in Cianjur district. Formulation of the issues raised in this study.The purpose of this study is to describe the efforts of Dikyasa units in implementing the Dikmas Lantas program in reducing the number of traffic violations committed by private employees in the Cianjur district police jurisdiction. This research uses descriptive qualitative research methods with Miles and Huberrman's data analysis techniques. Data collection techniques used in this study used the method of observation, in-depth interviews, and documentation. The validity of the data used in research uses triangulation of resources, techniques, time, and theory. Based on the results of the study explained that the implementation of Dikmas Lantas by the Unit of the Traffic Unit in preventing traffic violations has not been maximized. Constraints include internal and external factors. Internal factors that influence are the budget, personnel, and infrastructure, while external factors that influence are public awareness in a lack of orderly traffic, lack of support from the company.